CAGE19-2 Cruise Report: Hunting gas flares and launching seafloor observatory - Andreassen, Karin; Patton, Henry; Mattingsdal, Rune; Moser, Manuel; Cooke, Frances A.; Jansson, Per; Argentino, Claudio (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2023)
The cruise was part of the Centre of Excellence(SFF) Centre for Arctic Gas Hydrate, Environment and Climate Climate (CAGE) at UiT – The Arctic University of Norway. It was partly supported by The Norwegian Petroleum Directory (NPD). The cruise had the following scientific objectives: Identification of gas seepage associated with assumed hydrocarbon reservoirs subcropping the sea floor due to erosion of overlying cap rocks.Identification of gas seepage related to leakage along faults breaching the seafloor.Acqusition of multibeam, subbottom profiler-, seismic data and samples of gas in water and sediments for cross disciplinary investigations by CAGEDeployment of seafloor observatory and oceanographic studies west of Prins Kars Forland The cruise may be known as: CAGE19_2